Question Show that, with V = 4/5c, the Lorentz transformation of the equations, t^prime = y(V) (t-(v/c^2)x) and x^prime = y(V) (x-Vt). (where y(V) = the Lorentz factor). can be written as ct^prime = 5/3ct - 4/3x and x^prime = 5/3x - 4/3ct Relevant equations y(V) = 1/(sqrt1-(V/c)^2) The attempt at a solution I have calculated y(V) = 5/3 (if V = 4/5c) and i can see how the left hand term in each equation becomes 5/3ct and 5/3x respectivley. But i cant figure where the 4/3 term comes from?? or how to derive it?